Correction: Depression in the COVID-19 endemic era: Analysis of online self-disclosures by young South Koreans. - Seoyoung Kim; TaeYoon Aum; Dong-Gwi Lee (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0314881.].